Tomato Suspension Agreements and the Effects on Market Prices and Farm Revenue - Zhengfei Guan; Dong Hee Suh; Feng Wu (EDIS)
The production capacity of the US tomato industry has decreased significantly in the past decade. The US Department of Commerce and the Mexican tomato industry negotiated and signed several Suspension Agreements that set floor prices for imported Mexican fresh tomatoes to protect the US domestic industry. This 4-page article written by Zhengfei Guan, Dong Hee Suh, and Feng Wu and published by the UF/IFAS Food and Resource Economics Department provides a review of the history of the suspension agreements and an analysis of their effects on the US tomato industry. http://edis.ifas.ufl.edu/fe1025